Nalar Inklusif Ayat-ayat Kebebasan Beragama dalam Tafsir Al-Mishbah - Nor Salam (Universitas Muhammadiyah Malang, 2018)
This article examines the inclusive reasoning in the interpretation of Al-Misbah which specifically explores the verses of religious freedom and their implications in realizing awareness of the plurality of religion and belief in Indonesia. This manuscript begins with a sketch of the interpretation of Al-Misbah as one of the local interpretations that has been produced by al-Quran interpreter M. Quraish Shihab, then continues with a discussion of the interpretation of verses on religious freedom and an analysis of the tendencies of theological reasoning. Inclusive reasoning as seen in the interpretation of Al-Mishbah has its own relevance in developing Islamic attitudes that are able to respect and realize diversity. The model of open interpretation as practiced by Quraish Shihab provides new hope in encouraging a harmonious life between religious communities by sticking to their respective beliefs.